Aortic Bypass Surgery Simultaneously Performed with Coronary Artery Bypass Grafting and Mitral Valve Replacement in a Patient with Takayasu Arteritis: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Takayasu Arteritis; Aortabisubklavian Bypass; Coronary Artery Disease.